Rail Connected City-Regions: the Significance of Concerted Policies and Alternative Funding Options - Alexandros Deloukas (European Regional Science Association (ERSA), 2006)
One should not be enthusiastic of Far East mega-cities easily sustaining urban rail systems to understand that high densities slow down land consumption and increase ridership. An objective of the paper is to investigate the case of a mutually supportive land use and urban rail planning in two European cities. A parallel objective is to demonstrate that singular measures like urban rail stations or dense mixed uses are not sufficient to achieve a sustainable growth. The macro-connectivity of the city-region by rail as well as local parking constraints are important factors for successful sustainability. A particular (chrono-)logical planning sequence of action packages is suggested, in order to maximize the desired impacts. Next to the conceptual part, two relevant case studies are demonstrated. First, the Swiss City-Rail project of Bern. It concerns the two employment poles Ausserholligen west of, and Wankdorf east of the Central Station, where suburban rail interchanges are planned. Each pole will contain a development of 600.000 sq.m. Gross Floor Area of mixed uses, staged up to 2020. The wide range of concerted policies effectuated is analysed. Second, the case of Athens, one of the seven European mega-cities with more than 4 mi. inhabitants is discussed. Within the framework of the Metro Development Study (MDS), a multimodal transportation plan for Athens with the horizon 2020 has been developed. A calibrated Garin-Lowry land use – transportation model forecasts job and population figures at the level of 1230 traffic zones. The MDS 2020 plan contains 106 km metro, 46 km tramway, and 328 km suburban rail. High urban rail investments have already taken place in Athens, also in view of the Olympic Games. The paper discusses planning opportunities for concentrated service development at suitable rail interchanges proposed by the MDS. Two types of structural actions are considered. First, upzoning and new development around three suburban rail interchanges, especially along the suburban rail corridor leading from Athens to the Airport. A recent mall development in one of these interchanges is critically discussed. Rail use is better suited for employees and people seeking entertainment than shopping in this respect. Second, rezoning and recycled development at built-up areas around three peripheral metro interchanges, while protecting the existing housing. Finally, a comparative review of the planning frameworks in Bern and in Athens is performed, with a special emphasis on revealed planning deficits.
Keywords: 330